2012
DOI: 10.1111/j.1462-5822.2012.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans leukotoxin cytotoxicity occurs through bilayer destabilization

Abstract: Summary The Gram-negative bacterium, Aggregatibacter actinomycetemcomitans, is a common inhabitant of the human upper aerodigestive tract. The organism produces an RTX (Repeats in ToXin) toxin (LtxA) that kills human white blood cells. LtxA is believed to be a membrane-damaging toxin, but details of the cell surface interaction for this and several other RTX toxins have yet to be elucidated. Initial morphological studies suggested that LtxA was bending the target cell membrane. Because the ability of a membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 65 publications
1
56
0
Order By: Relevance
“…Standard curves with increasing concentrations of HlyA identified the EC 50 of the toxin. The EC 50 for LtxA was found at a concentration of 0.122 g ml Ϫ1 , which is slightly more potent in this purification than what was previously published (13). The EC 50 for HlyA varies and has to be determined every experimental week because of the faster degradation of protein activity.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…Standard curves with increasing concentrations of HlyA identified the EC 50 of the toxin. The EC 50 for LtxA was found at a concentration of 0.122 g ml Ϫ1 , which is slightly more potent in this purification than what was previously published (13). The EC 50 for HlyA varies and has to be determined every experimental week because of the faster degradation of protein activity.…”
Section: Methodsmentioning
confidence: 62%
“…The EC 50 for LtxA was found at a concentration of 0.122 g ml Ϫ1 , which is slightly more potent in this purification than what was previously published (13). The EC 50 for HlyA varies and has to be determined every experimental week because of the faster degradation of protein activity. The amount of active protein which corresponded to EC 50 in our preparation has been determined to be 25 ng ml Ϫ1 (4 Statistics.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…When considering this option, one has to acknowledge that true pore formation has been questioned for both toxins, in particular LtxA (36,43). Nevertheless, it is well established that both HlyA and LtxA are membrane-damaging toxins (44 -49) but conclusive details regarding their membrane interaction are unknown for both proteins as structural models are currently lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Patch clamp studies on HL-60 cells supported this by showing a large conductance and collapse of the membrane potential when LtxA was present (64). Recent data on T lymphocytes and artificial membranes argues against direct pore formation and suggest that the cytotoxicity of LtxA originates from membrane destabilization without the formation of transmembrane pores (36,43). The latter studies showed membrane interaction with artificial membranes, and the conclusion from these studies was that LtxA binds via two steps: (i) membrane association and (ii) membrane destabilization, which occurs through a modification of the bilayer structure demonstrated by leakage of dye (calcein or 8-aminonaphtalene-1,3,6-trisulfonic acid/p-xylene-bis(N-pyridium bromide) (ANTS/DPX)).…”
Section: Discussionmentioning
confidence: 99%